The Influence of Motivation and Work Environment on the Performance of Service Unit Employees at Bank BNI Syariah Bogor Branch Office - Devy Pratiwi Rahmawati; Dimas Ari Darmantyo; Sumardjono Sumardjono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine and analyze the influence of motivation and work environment on employee performance at PT Bank BNI Syariah Bogor Branch Office. The type of research used is associative research with data collection methods using questionnaires. The data analysis model used is multiple linear regression. With a saturated sample of 35 respondents who are employees of the service unit at Bank BNI Syariah Bogor Branch Office, this study shows that the performance of service unit employees at PT Bank BNI Syariah Bogor branch office is 70.2% influenced by motivation and work environment variables while for 29,8% influenced by other variables not included in this study. Variables of motivation and work environment simultaneously affect employee performance.